Comparison of giving ephedrine 30 Î¼g/kgbw iv and lidocaine 2% 40 mg iv to educe pain induction propofol 2 mg/kgbw iv in general anesthesia - Yusmein Uyun, Mujahidin Bambang Suryono (Universitas Gadjah Mada, 2013)
The administration of propofol often causes burning sensation in the area of injection. There have been efforts to reduce discomfort, but the result remains unsatisfactory. The main purpose of this study is to find objective evidence of whether the administration of ephedrine 30Î¼g/kgBB IV is more effective than 40mg 2% lidocaine in order to reduce propofol 2mg/kgBB injection pain.This study was conducted in the double blind Randomized Controlled Trial (RCT) to 128 patients, with the range of age 18-60 years, physical status ASA I and II, BMI 17.5 â 24.5 kg/m2 which had been done elective surgery in the Intergrated Surgery Center of Dr. Sardjito Hospital Yogyakarta and other education network (Banyumas Hospital, Panembahan Senopati Bantul Hospital, Orthopedi Solo Hospital, Saras Husada Purworejo Hospital) and carried out in 2-4 months, general anaesthesia has been done with endotracheal intubation technic. Subjects have been divided into 2 groups, group A (lidokain 40 mg) and group B (efedrin 30Î¼g/ kgBB). All of the patients have been given at the vena sefalikabasalika with 18G needle and RL. After one of the drugs has been given, the patient will be inducted with propofol 60 seconds later. The measurement of discomfort caused by propofol injection has been marked with discomfort scoring system (score 0-3), the blood pressure measurement has been taken before and after propofol administration. The results showed no statistically significant difference in the two study groups (2% lidocaine 40 mg IV vs ephedrine 30Î¼g/kgbb IV) on pain response measured when patients received propofol 2mg/kgbb IV, p > 0.05 (P = 0.068) In group A there were 52 patients (81.3%), pain-free, while for group B there were 59 patients (92.2%). The pain response obtained was varies, in group A obtained a scale of 1-3, while in group B obtained a scale of 1-2. It can be concluded that administration of IV ephedrine 30Î¼g/kgBB is not a significantly different effect compared with 2% lidocaine 40 mg IV to prevent response to pain during injection of propofol 2 mg / kg IV, P> 0.05 (P = 0.068), but clinically group B have the ability to eliminate pain in 59 patients (92.2%) compared with group A in 52 patients (81.3%), while the possibility of causing pain in group A were 12 patients (7.8%) and group B were 5 patients (18.7%).Keywords: Pain, injection, propofol, lidocaine, ephedrine.